How Do Somatosensory Deficits in the Arm and Hand Relate to Upper Limb Impairment, Activity, and Participation Problems After Stroke? A Systematic Review. Issue 9 (1st September 2014) - Meyer, Sarah; Karttunen, Auli H.; Thijs, Vincent; Feys, Hilde; Verheyden, Geert
Abstract : Background: The association between somatosensory impairments and outcome after stroke remains unclear. Purpose: The aim of this study was to systematically review the available literature on the relationship between somatosensory impairments in the upper limb and outcome after stroke. Data Sources: The electronic databases PubMed, CINAHL, EMBASE, Cochrane Library, PsycINFO, and Web of Science were systematically searched from inception until July 2013. Study Selection: Studies were included if adult patients with stroke (minimum n=10) were examined with reliable and valid measures of somatosensation in the upper limb to investigate the relationship with upper limb impairment, activity, and participation measures. Exclusion criteria included measures of somatosensation involving an overall score for upper and lower limb outcome and articles including only lower limb outcomes. Data Extraction: Eligibility assessment, data extraction, and quality evaluation were completed by 2 independent reviewers. A cutoff score of ≥65% of the maximal quality score was used for further inclusion in this review. Data Synthesis: Six articles met all inclusion criteria. Two-point discrimination was shown to be predictive for upper limb dexterity, and somatosensory evoked potentials were shown to have predictive value in upper limb motor recovery. Proprioception was significantly correlated with perceived level of physical activity and social isolation and had some predictive value in functional movements of the upper limb. Finally, the combination of light touch and proprioception impairment was shown to be significantly related to upper limb motor recovery as well as handicap situations during activities of daily living. Limitations: Heterogeneity of the included studies warrants caution when interpreting results. Conclusions: Large variation in results was found due to heterogeneity of the studies. However, somatosensory deficits were shown to have an important role in upper limb motor and functional performance after stroke.